Therapeutic approaches to haematological malignancies in adolescents and young adults. (6th September 2013) - Place, Andrew E.; Frederick, Natasha N.; Sallan, Stephen E.
Summary Tremendous strides have been made in improving the outcomes of haematological malignancies (HM) over the last three decades, but adolescents and young adult (AYA) patients have not benefitted equally compared to younger and older patients. Excellent outcomes in Hodgkin lymphoma have allowed tailoring of highly effective regimens that limit the incidence of late effects. Early successes in paediatric acute lymphoblastic leukaemia set the stage for a series of studies in young adults utilizing a paediatric‐type treatment strategy. These studies have determined that AYAs benefit from paediatric‐type chemotherapy regimens. Despite the increased incidence of acute myeloid leukaemia and non‐Hodgkin lymphoma in the AYA age group, optimal strategies for these patients have not been systematically pursued. There is renewed interest in improving HM outcomes in AYA patients and this will rely on the development of clinical trials that specifically target these patients. Understanding and addressing the unique psychosocial challenges of this population will be critical in supporting this endeavor.